ChemInform Abstract: Copper‐Mediated Aerobic Oxidative Synthesis of Benzimidazo Fused Quinazolines via a Multicomponent Approach. Issue 8 (February 2016) - Rai, Byanju; Kumar, Promod; Kumar, Atul
Abstract: The synthesis of the title quinazolines involves the formation of three C—N bonds starting from the azidation of the haloaryl educts with sodium azide followed by in situ conversion of these azides into aryl amines, which on condensation with various benzaldehydes undergo oxidative cyclization affording benzimidazo[1, 2‐c]quinazoline derivatives in good to excellent yields.